Utilization of Oil Palm Fiber Agricultural Waste on the Mechanical Characteristics of AC-WC Asphalt Mixtures Using the Dry-Mix Method - Karina Putri Wijaya; Tri Sudibyo (Jurnal Teknik Sipil dan Lingkungan, 2026)
Early pavement distress due to permanent deformation and fatigue cracking remains a major challenge for flexible pavement infrastructure in Indonesia, particularly under high traffic loading and tropical climatic conditions. Meanwhile, the Indonesian palm oil industry generates more than 23 million tons annually of Empty Fruit Bunch (EFB), which has not yet been optimally utilized as agro-industrial waste. This study investigates the utilization of EFB fibers treated with NaOH alkali and coated with asphalt emulsion as an additive in Asphalt Concrete Wearing Course (AC-WC) mixtures using the dry-mix method. The experimental variables include two fiber lengths (0.5 cm and 1 cm) and three fiber contents (0.2%, 0.4%, and 0.6%), while maintaining a constant Optimum Asphalt Content (OAC) of 6%. Marshall testing was conducted in accordance with SNI 2489:2018, referring to the Bina Marga General Specifications 2025. The results indicate that fiber incorporation enhances stability up to 1,748.80 kg and increases the Marshall Quotient (MQ) to 530.24 kg/mm, compared to the control mixture with stability of 1,666.16 kg and MQ of 512.33 kg/mm. Volumetric analysis shows a reduction in VIM (4.14-4.32%) and VMA (18.76-18.86%), along with an increase in VFA (77.08-77.92%). The Optimum Fiber Content (OFC) is identified at 0.5 cm fiber length with 0.4% fiber content, yielding stability of 1,748.80 kg, MQ of 530.24 kg/mm, VFA of 77.66%, and an Immersion Residual Strength (IRS) of 90.79%.